PROBLEMATIKA PENGURUSAN PERIZINAN BERUSAHA TERINTEGRASI SECARA ELEKTRONIK BERBASIS RISIKO BAGI PERSEROAN TERBATAS - Caesar Ali Syabana (2023)
Risk-based electronically integrated business license or Online Single Submission Risk Based Approach (OSS RBA) is a Business Permit issued by the OSS Institution to Business Actors. The management of risk-based electronic integrated business licensing is regulated in Government Regulation Number 5 of 2021 concerning Implementation of Risk-Based Business Licensing. The emergence of risk-based integrated electronic business licensing as a breakthrough for the new business licensing system has not been able to solve the problem of the business licensing integration process for Limited Liability Companies. The problems discussed in this study are, first, how are the problems of managing electronically integrated business licenses based on risk. Second, how should the risk-based electronically integrated business licensing arrangements for Limited Liability Companies. This study uses a type of normative juridical research with a statutory approach (statute approach), conceptual approach (conceptual approach). The results of this study draw the conclusion that managing business licensing through the OSS-RBA system still leaves several problems such as regulations, institutions, and digitalization of the OSS RBA system. Management of business licensing should be one door integrated into the OSS RBA system. In addition, it is also necessary to integrate the management of business licenses using third party service providers. The author's suggestion to the Government is to improve the content of implementing regulations regarding OSS RBA and improve the digitization of the OSS RBA system. Furthermore, the Government and related institutions integrate all one-stop licensing systems through the OSS RBA system.